From sabers to spikes: A newfangled reconstruction of the ancient, giant, sexually dimorphic Pacific salmon, †Oncorhynchus rastrosus (SALMONINAE: SALMONINI) - Claeson, Kerin M.; Sidlauskas, Brian L.; Troll, Ray; Prescott, Zabrina M.; Davis, Edward B. (PLOS ONE, 2024)
The impressive †Oncorhynchus rastrosus of the Pacific Northwest’s Miocene and Pliocene eras was the largest salmonid ever to live. It sported a hypertrophied premaxilla with a pair of enlarged teeth which the original describers reconstructed as projecting ventrally into the mouth, leading them to assign the species to “Smilodonichthys,” a genus now in synonymy. Through CT reconstruction of the holotype and newly collected specimens, we demonstrate that the famed teeth projected laterally like tusks, not ventrally like sabers or fangs. We also expand the original description to characterize sexual dimorphism in mature, breeding individuals. Male and female †Oncorhynchus rastrosus differ in the form of the vomer, rostro-dermethmoid-supraethmoid, and dentary, much as do other extant species of Oncorhynchus. Male specimens possess a more elongate vomer than do females, and female vomers have concave ventral surfaces and prominent median dorsal keels. The dentary of females has no evidence of a kype, though some specimens of †O. rastrosus have a non-uniform density mesial to the tooth bed, which we interpret as a male kype. Unlike extant Oncorhynchus, male and female †O. rastrosus do not differ in premaxilla shape. Because male and females possess hypertrophied premaxillae and lateral premaxillary spikes, the former common name “Sabertoothed Salmon” no longer reflects our understanding of the species’ morphology. Accordingly, we redub †O. rastrosus the Spike-Toothed Salmon and postulate that its spikes were multifunctional, serving as defense against predators, in agonism against conspecifics, and as a practical aid to nest construction.